2018
DOI: 10.1063/1.5046844
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain analysis of pyroelectric response in silicon-doped hafnium oxide (HfO2) thin films

Abstract: The pyroelectric response of polycrystalline, Si-doped HfO2 layers with a thickness of 20 nm is investigated in a frequency range of 2 Hz to 20 kHz. Local Joule heating of the pyroelectric material by a deposited nickel strip is used to achieve fast thermal cycles. Over the whole frequency range, a distinct pyroelectric response is registered. A pyroelectric coefficient of −72 μC/m2K is obtained at a frequency of 10 Hz, which is in good agreement with earlier low-frequency measurements. The pyroelectric curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…For the field‐cycled sample, a large pyroelectric coefficient of −(1442 ± 10) μC m −2 K −1 is obtained at 0 V with respect to device footprint, which corresponds to a planar value of –74 μC m −2 K −1 with an area enhancement factor of 19.5. This is similar to earlier measurements with planar samples and a similar manufacturing technique, indicating a successful vertical integration of the pyroelectric Si‐doped HfO 2 films. At increasing voltages, the pyroelectric response decreases slightly, reaching −(1042 ± 23) μC m −2 K −1 at 3 V. The phase of the total current is displayed in Figure f, indicating values close to the ideal value of ±90°, proving the pyroelectric origin of the registered current.…”
Section: Pyroelectric Coefficients Dielectric Permittivity Heat Capsupporting
confidence: 90%
See 3 more Smart Citations
“…For the field‐cycled sample, a large pyroelectric coefficient of −(1442 ± 10) μC m −2 K −1 is obtained at 0 V with respect to device footprint, which corresponds to a planar value of –74 μC m −2 K −1 with an area enhancement factor of 19.5. This is similar to earlier measurements with planar samples and a similar manufacturing technique, indicating a successful vertical integration of the pyroelectric Si‐doped HfO 2 films. At increasing voltages, the pyroelectric response decreases slightly, reaching −(1042 ± 23) μC m −2 K −1 at 3 V. The phase of the total current is displayed in Figure f, indicating values close to the ideal value of ±90°, proving the pyroelectric origin of the registered current.…”
Section: Pyroelectric Coefficients Dielectric Permittivity Heat Capsupporting
confidence: 90%
“…Characterization of the pyroelectric effect in Si‐doped HfO 2 revealed the potential of this material system for energy conversion applications, with published pyroelectric coefficients of –84 and –46 μC m −2 K −1 . Recent reports showed that the pyroelectric coefficient remains stable in a temperature range from 20 to 160 °C and for rapid temperature cycles up to 20 kHz . Deep‐etched silicon structures have formed the basis of high‐surface‐area capacitors for energy storage applications and high‐density ferroelectric memory .…”
Section: Pyroelectric Coefficients Dielectric Permittivity Heat Capmentioning
confidence: 99%
See 2 more Smart Citations
“…A SiO 2 layer with a thickness of 30 nm was used to electrically insulate the MFM stack from the overlapping 100 nm Ni film, which served as a resistive heater with a resistance of 13 Ohm. Further details of deposition and test structure manufacturing are reported elsewhere 28. Samples were mounted on a printed circuit board using electrically conductive silver glue and wire bonding.…”
Section: Methodsmentioning
confidence: 99%